I invented the modern age : the rise of Henry Ford - Snow, Richard, 1947- (New York : Scribner, 2013)
An account of Henry Ford's invention of the Model-T offers insight into his mechanical talents and pioneering work in internal combustion, describing his impact on American culture and the perplexing subsequent changes in his personality.
A homecoming -- "My toys were all tools" -- Clara -- Working from the ground up -- What Edison said -- "Glory and dust" -- The seven-million-dollar letter -- Ford finds his greatest asset -- Inventing the universal car -- The man who owned every car in America -- The Model T takes over -- Terrible efficiency -- The five-dollar day -- Simple purposes -- The expert -- The international Jew -- The end of the line -- Epilogue.
Includes bibliographical references (p. 341-346) and index.
Keywords: Ford, Henry, -- 1863-1947.; Automobile engineers -- United States -- Biography; Industrialists -- United States -- Biography; Automobile industry and trade -- United States -- History; Ford Model T automobile -- History; BIOGRAPHY & AUTOBIOGRAPHY / Historical; HISTORY / United States / 20th Century; HISTORY / Civilization